2004
DOI: 10.1111/j.1432-1033.2004.04346.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an Escherichia coli system for cell‐free synthesis of selectively 15N‐labelled proteins for rapid analysis by NMR spectroscopy

Abstract: Cell-free protein synthesis offers rapid access to proteins that are selectively labelled with [ 15 N]amino acids and suitable for analysis by NMR spectroscopy without chromatographic purification. A system based on an Escherichia coli cell extract was optimized with regard to protein yield and minimal usage of 15 N-labelled amino acid, and examined for the presence of metabolic by-products which could interfere with the NMR analysis. Yields of up to 1.8 mg of human cyclophilin A per mL of reaction medium were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
108
1
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 36 publications
3
108
1
3
Order By: Relevance
“…The larger component corresponds to a form of the protein that retains the N-formyl group on the N-terminal methionine residue (calculated M r 19 249.6), and the smaller is the mature protein produced after deformylation (calculated M r 19 221.6). This is in accord with the results of a previous NMR study, in which amide resonances could be observed for the N-terminal methionine as well as for the following residue in hCypA [18], indicating that our S30 extract is deficient in peptide deformylase activity [6].…”
Section: Esi-ms Of Dopa-labelled His 6 -Ppibsupporting
confidence: 93%
See 2 more Smart Citations
“…The larger component corresponds to a form of the protein that retains the N-formyl group on the N-terminal methionine residue (calculated M r 19 249.6), and the smaller is the mature protein produced after deformylation (calculated M r 19 221.6). This is in accord with the results of a previous NMR study, in which amide resonances could be observed for the N-terminal methionine as well as for the following residue in hCypA [18], indicating that our S30 extract is deficient in peptide deformylase activity [6].…”
Section: Esi-ms Of Dopa-labelled His 6 -Ppibsupporting
confidence: 93%
“…1EMA) [22]. The first two proteins had previously been shown to be produced in good yield in the in vitro reaction [5,6,18,23].…”
Section: Protein Synthesis In the Presence Of Dopamentioning
confidence: 99%
See 1 more Smart Citation
“…2 These approaches have been used for the synthesis of proteins containing high levels of fluorinated, 5 dehydro 6 and isotopically-labelled 7,8 amino acids, as well as 3,4-dihydroxy-Phe 9 and seleno-Met 10 in place of Tyr and Met, respectively.…”
mentioning
confidence: 99%
“…7,9,20 The native protein was prepared using each of the 20 normal amino acids. Incorporation of other amino acids was investigated through their substitution for one of the 20.…”
mentioning
confidence: 99%